Análisis conceptual del descuento de facturas y su viabilidad en una empresa de costarricense - Gómez Molina, Max (1996)
The rapid and constant changes takíng place today around the world, along wíth the new openings for commercial opportunities in the international markets are driving countries such as Costa Rica to become more competítive each day, thus demanding an ever increasing financial support. With this objective, a new financial sector dedicated to factoring has developed ín our country wíth the aim of providing the client with a service for discount on account prepayment and collecting. In many countríes with more developed fínancial markets, such as the US, this is an already weil established activity. Nevertheless, in the case of Costa Rica, this activity is still relatively young as it started only sorne fifteen years ago. Yet, it is becoming more popular every day among local business people as it proves an effective way for obtaining credít easily. Business firms in all areas buy the service provided by these factoring companies, especially those in the commercial and industrial sectors. Although most óf the that procure this service are small or medium, there are also several larger companies that resort to it, such as in the case of transnational companies which recur to it in cases where their head offices deny them permission to become indebted and thus jeopardize their liquidity. Factoring is an option that is also available to new and expanding companies. For instance, for a company that is facing temporary liquídíty problems and ís thus unable to cover its payroll or payments to its suppliers, factoring could prove an efficient short-term alternative to solve that campany's problems. Upen requesting factoríng services, the requestíng company is subjected to a meticulous study. First, íts references are verified, and then, the accounts of all its clients are tlloroughly analyzed. Once a line of credit is granted to the requesting company, and once it has submitted the list...